ANALISIS PENGARUH MANAJEMEN TALENTA DAN GLOBAL MINDSET TERHADAP KINERJA KARYAWAN DAN TURNOVER INTENTION DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT. Cipta Busana Mandiri Demak) - Kusumowardani, Ayu; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to see the impact of Â talent management and global mindset to the performance of employee and turnover intention regarding commitment of organization as an intervening variable to the employee of Â PT. Cipta Busana Mandiri Demak.This study used software smart PLS 2.0.m3 version (Partial Least Squer) as the methodology in data analysis. The sample of this study are employee of PT.Cipta Busana Mandiri Demak with 88 respondents. While data was collected through questioner, surveys, interview and literature review.The result of this study indicates: 1) talent management has positive and significant impact to the commitment of organization 2) global mindset has negative and significant impact to the commitment of organization, 3 )talent management has negative and significant impact to the turnover intention, 4) global mindset has no significant and negative impact to the performance of employee 5) commitment of organization has negative and significant impact to turnover intention, 6) commitment of organization has positive and significant impact to the performance of employee.